PENGENDALIAN KUALITAS AIR PADA PERUSAHAAN DAERAH AIR MINUM TIRTA MEULABOH UNTUK MENINGKATKAN LAYANAN KEPADA MASYARAKAT - Fitriadi Fitriadi (Jurnal Optimalisasi, 2015)
Water is a basic need that is very important for humans and other living creatures. Drinking water is water whose quality meets health requirements and can drink, it was clean water is water used for daily necessities whose quality meets the requirements of health and can be taken if it has been cooked. The quality of products is one of the most important factors affecting the company's progress, as well as for the water company. In this regard discuss about water quality control if it meets quality standards or not. Quality Control of water in accordance with the standardization and quality standards are allowed very closely related to the level of customer satisfaction. Control of the quality of a product can be done by measuring the different variables that influence it. One way to measure and determine the quality of a product is by using the Taguchi method is done with the design parameters is one of the design phase of a product or process. So hopefully by doing this study water quality PDAM Tirta Meulaboh can be controlled and can be controlled which can certainly improve water services to the people of Aceh Barat.Kata Kunci : Water, Quality Control, Customer Satisfaction, Taguchi.